SYSTEMATIC LITERATURE REVIEW: EVALUASI YURIDIS KLAUSUL EKSONERASI DALAM KONTRAK BAKU E-COMMERCE - Dhika Fajri Ramadhan; Alfito Pragaswara; Naila Hairin Nisa; Agus Septima Ridwan (INTELIGENSIA MEDIA, 2026)
This study aims to evaluate the validity of exculpatory clauses in standardized e-commerce contracts and to assess the civil liability of platforms under Indonesian legal norms. The core problem examined is the widespread inclusion of liability-waiver clauses within the terms and conditions of online shopping applications, which places consumers in a weak position and generates legal uncertainty. The method employed is a Systematic Literature Review of fourteen accredited national legal journal articles published over the past ten years, involving coding, synthesis, and normative assessment against statutory texts. The findings reveal an academic consensus that exculpatory clauses within the click-wrap mechanism violate the requirements for a valid agreement under Article 1320 of the Indonesian Civil Code because they arise from a defect of will through abuse of circumstances, while also contravening the prohibition in Article 18 of the Consumer Protection Law and are therefore void by law. Consequently, the platform still bears full liability based on breach of contract and must compensate the consumer's entire material loss. This study provides a firm juridical evaluation map for practitioners and academics regarding the liability limits of digital platforms in Indonesia.